Differential Impact of Cyberbullying and Verbal Bullying on Depression Levels in Late Adolescence - Agastya Fernanda; Eleadora Carla (PELNUS | Pen en Light for Natural Union of Science, 2023)
Bullying, in its various forms, poses a significant threat to adolescent mental health. This research delves into the distinct psychological impacts of cyberbullying and verbal bullying by examining their associations with depression levels among late adolescents. A mixed-methods approach was employed, encompassing quantitative surveys and qualitative interviews with a diverse sample of late adolescents. Participants were drawn from various socio-economic backgrounds and educational settings to ensure representation. Quantitative analysis revealed statistically significant differences in depression levels between victims of cyberbullying and verbal bullying. Cyberbullying victims exhibited notably higher levels of depressive symptoms compared to those experiencing verbal bullying. Qualitative insights enriched the findings, elucidating the nuanced experiences and emotional distress faced by victims. Cyberbullying victims described feelings of isolation, powerlessness, and constant fear, stemming from the relentless and anonymous nature of online harassment. In contrast, victims of verbal bullying expressed immediate emotional pain, humiliation, and social ostracization within their immediate physical environments. The observed differences underscore the unique psychological toll of cyberbullying and verbal bullying on adolescent mental health. The pervasive nature, anonymity, and prolonged exposure inherent in cyberbullying intensify emotional distress, contributing to more severe depressive outcomes. These findings hold crucial implications for tailored interventions, societal awareness, and support systems aimed at mitigating the detrimental impact of bullying on adolescent mental health.